A CLR Virtual Machine Based Execution Framework for IEC 61131-3 Applications (Informatica, 2019)
The increased need of flexibility of automation systems and the increased capabilities of sensors and actuators paired with more capable bus systems, pave the way for the reallocation of IEC 61131-3 applications away from the field level into so-called compute pools. Such compute pools are decentralised with enough compute power for a large number of applications, while providing the required flexibility to quickly adapt to changes of the applications requirements. The paper proposes a framework able to deploy IEC 61131-3 applications to multiple computing platforms based on CLR VM; it uses C# language as intermediate code. The software solution proposed by the authors does not require any modifications of the IEC 61131-3 applications. Current literature does not provide solutions like that here presented; due to the spread current use of C# language in the development of industrial applications, adoption of the proposed solution seems very attractive. The paper will deeply describe the software implementation and will also present an analysis about the capability of the proposed framework to respect real-time constraints of the industrial processes, mainly focusing on the periodic ones.